RIPK1 in the inflammatory response and sepsis: Recent advances, drug discovery and beyond - Liu, Xiaoyu; Tang, A-Ling; Chen, Jie; Gao, Nan; Zhang, Guoqiang; Xiao, Cheng (Frontiers in Immunology, 2023)
Cytokine storms are an important mechanism of sepsis. TNF-α is an important cytokine. As a regulator of TNF superfamily receptors, RIPK1 not only serves as the basis of the scaffold structure in complex I to promote the activation of the NF-κB and MAPK pathways but also represents an important protein in complex II to promote programmed cell death. Ubiquitination of RIPK1 is an important regulatory function that determines the activation of cellular inflammatory pathways or the activation of death pathways. In this paper, we introduce the regulation of RIPK1, RIPK1 PANoptosome's role in Inflammatory and sepsis, and perspectives.